Homeoviscous properties implicated by the interactive effects of pressure and temperature on the hydrothermal vent crab Bythograea thermydron - Airriess, C; Childress, J J (Biological Bulletin, 1994)
Specimens of the hydrothermal vent crab Bythograea thermydron, collected from 13{\{}deg{\}} N on the East Pacific Rise, were exposed to pressures greater than those in their natural habitat over a range of temperatures to assess how increased hydrostatic pressure affects a species that requires high pressure to survive. We measured heart beat frequency and contraction waveform at pressures ranging from 28 MPa (normal environmental pressure for this species) to 62 MPa at 5{\{}deg{\}}, 10{\{}deg{\}}, and 20{\{}deg{\}}C. At 5{\{}deg{\}}C, increased hydrostatic pressure induced bradycardia or acardia in conjunction with marked disruption of the ventricular contraction waveform. The animals did not survive following decompression. The effects of increased pressure were less pronounced at 10{\{}deg{\}}C and almost negligible at 20{\{}deg{\}}C. Our results support previous findings at subambient pressures which suggest that the lipid bilayers of cell and organelle membranes are the primary sites affected by short-term pressure variation in deep-sea organisms. We also found evidence of an adaptive mechanism of pressure temperature interaction in these animals from the eurythermic habitat of the hydrothermal vents.
Keywords: HOV Alvin (Human Occupied Vehicle)